The Influence of Financial Performance and Capital Structure on Tax Avoidance Strategies - Ajay Susanto; Yunia Oktari (eCo-Buss, 2024)
This research seeks to examine how profitability, capital intensity, and sales growth impact tax avoidance practices. Employing a quantitative methodology, the study centres on companies within the food and beverage subsector that are publicly traded on the Indonesia Stock Exchange (IDX) during 2020 to 2023. The sample consisted of 76 companies, which were selected by the purposive sampling method over four years, covering 19 companies. The data was analysed with SPSS version 29 software through a descriptive statistical approach, classical assumption testing, and hypothesis testing. The multiple linear regression technique is applied to the secondary data collected. The results of the analysis revealed that profitability (ROA), had a significant impact on tax avoidance with a significance level of less than 0.05. In contrast, the variables of sales growth and capital intensity showed insignificant results (significance value of more than 0.05), indicating that they did not have an impact on tax avoidance individually. However, simultaneously, profitability, capital intensity, and sales growth together have a significant impact on tax avoidance, with a significance value below 0.05.